Biological conversion of methane to methanol at high H2S concentrations with an H2S-tolerant methanotrophic consortium. (March 2023) - Jiang, Danping; Ge, Xumeng; Lin, Long; Chen, Zhou; Zhang, Quanguo; Li, Yebo
Abstract: To develop biological biogas to methanol conversion technology without costly hydrogen sulfide (H2 S) removal, a high H2 S tolerant methanotrophic consortium (HTMC), was enriched from an anaerobic digester effluent in presence of 5.64 g/m 3 H2 S in the gas phase. The HTMC can grow stably and produce methanol under conditions with CH4 /air mixtures containing 5.64 g/m 3 of H2 S. There is no significant ( p > 0.05) difference in cell yield or CH4 to methanol conversion efficiency between trials with different H2 S concentrations from 0 g/m 3 to 5.64 g/m 3 . Under optimal conditions, a cell yield of 0.333 g cells/g CH4, a methanol concentration of 0.28 mg/mL, and a CH4 to methanol conversion efficiency of 0.22 mol/mol were obtained, respectively. Besides methanotrophs (14.85%) and other bacteria, Cyanobacteria were also identified in the HTMC with a high abundancy (32.16%), which could broaden the application of HTMC for simultaneous utilization of CH4 and CO2 from raw biogas. Graphical abstract: Image 1